Green Economy, Technology, People and Industrial Tourism (Get Points) - Natita, Rendi Kusuma; Septiarini, Eka; Abdullah, Riono Aulia (International Journal of Research in Community Services, 2025)
Rapid technological and economic advancement has resulted in the proliferation of environmentally detrimental products and consumption patterns, significantly impacting the environment. Plastic pollution has emerged as a critical environmental concern, with Indonesia ranking fifth among the world's largest plastic waste producers. Annually, Indonesia generates approximately 7.8 million tons of plastic waste, of which 4.9 million tons are inadequately managed. For an extended period, Indonesia relied on a linear economic model characterized by a "take-use-dispose" approach. However, a transition towards a circular economic model is currently underway. In response to the significant environmental challenge posed by plastic waste pollution in Indonesia, the government has strategically introduced the Green Economy initiative. This innovative framework, an integral component of Indonesias 2025-2045 Long-Term Development Plan (RPJPN), is founded upon a robust and balanced approach that prioritizes three core pillars: economic prosperity, social equity, and environmental sustainability. In response to these challenges, the researchers devised the "Get Points" program, an acronym for Green Economy, Technology, People, and Industrial Tourism. This program was implemented at Ekowisata Cimenteng, located in Cipageran, North Cimahi District. The primary objective of this initiative is to address plastic waste management concerns while simultaneously fostering economic growth within local communities and among stakeholders. The program was executed through an outreach methodology, accompanied by pre- and post-tests for evaluation purposes. Comparative analysis of the pre- and post-test results revealed a notable increase in participant comprehension of plastic waste management issues. This enhancement was achieved through the integration of financial management seminars, digital marketing workshops, and 3D printing workshops, thereby facilitating economic growth for Ekowisata Cimenteng, local communities and stakeholders.